(untitled) (International Journal of Engineering and Computer Science, 2014)
Various natural systems teach us that very simple individual organisms can create systems able to solve the complex problems like optimization. Ant Colony Optimization (ACO) is an agent-based technique, which simulates the natural behavior of ants and develops mechanisms of cooperation and learning. Ant Colony Optimization is a metaheuristic approach for solving hard combinatorial optimization problems. The main idea of ACO is to model a problem as the search for a minimum cost path in a graph. Ant Colony Optimization has been successfully applied to scheduling, vehicle routing, and the sequential ordering problems. A review of several Ant Colony Optimization algorithms is done in this paper.